Faith and Loyalty: Bosniaks and the Austro-Hungarian Empire (Context: Journal of Interdisciplinary Studies, 2025)
Dževada Šuško, Faith and Loyalty: Bosniaks and the Austro-Hunga- rian Empire, The International Institute of Islamic Thought, 2024, 218 str., ISBN 979-8891-930-43-8 (hardback) | ISBN 979-8891- 930-44-5 (paperback) | ISBN 979-8891-930-45-2 (ebook)